Germination requirements of Androsace villosa L. (Primulaceae) - Uludağ Üniversitesi/Fen-Edebiyat Fakültesi/Biyoloji Anabilim Dalı.; Uludağ Üniversitesi/Gemlik Asım Kocabıyık Meslek Yüksek Okulu/Bitkisel ve Hayvansal Üretim.; orcid:0000-0001-5441-037X; orcid:0000-0002-2680-9815; Arslan, Hülya; Kırmızı, Serap; Güleryüz, Gürcan; Sakar, Fatma Selcen; D-2584-2016; A-5538-2019; 7006712783; 6506756812; et al. (Acta Biologica Cracoviensia Series Botanica, 2011)
We investigated the germination requirements of Androsace villosa L. (Hairy Androsace), which spreads on limestone or granite screes or ledges of rocky or turfy slopes and hilltops of the alpine zone. With seeds collected from Uludag Mt. (Bursa, Turkey, 2200-2300 m a.s.l.), germination was studied in fresh seeds, seeds subjected to short-time moist chilling (15 d, +4 degrees C), to GA(3) (100, 150 and 250 ppm), and to chilling plus GA(3). The hormone and moist chilling treatments were carried out in continuous darkness (20 degrees C) and under a 12 h photoperiod at 20/10 degrees C. Seeds maintained in darkness gave higher germination percentages than seeds maintained under a photoperiod. Germination rates rose to 90-97% with 100-250 ppm GA(3) and short-time moist chilling in continuous darkness (20 degrees C). Seeds germinated rapidly under a combination of GA(3) and short-Lime moist chilling in continuous darkness, generally giving the lowest mean germination times (4.4-5.0 d) among the treatments.